The conflicting ways to dissect intra-industry trade - Andrey A. Gnidchenko (FIW - Research Centre International Economics, 2019)
Theoretical literature states that intra-industry trade (IIT) should be divided into horizontal and vertical flows (or trade in products with homogeneous and heterogeneous quality) that are influenced by different factors. Yet, the economists are still not sure about the proportion between horizontal and vertical IIT. Traditional approach relies on unit value as an indicator of product quality. However, it is associated with a number of problems such as arbitrariness of the threshold used to separate the types of trade. We propose the two alternative approaches to dissecting IIT: first, applying another product quality indicator (PRODY - per capita GDP associated with exporting a product) and, second, relying on countries' product-level differences in the revealed comparative advantage (RCA). We also argue in favor of the new continuous treatment of the index-based unit value approach (in the spirit of the overlap calculation of the IIT itself) that finally helps to get rid of the arbitrary thresholds problem. However, then we reject the PRODY- and RCA-based approaches due to an undesirable behavior (low correlation with the share of exports to other EU countries, low shares of horizontal IIT for homogeneous products and other features), while the performance of the continuous form of the index-based unit value approach is found to be in line with the traditional unit value approach. We also argue that the two index-based modifications are preferable to the traditional unit value approach due to the higher shares of horizontal IIT for homogeneous products. We conclude that the median share of horizontal IIT for EU countries is still unknown due to fundamental uncertainty about the dissecting approach. At the same time, relative positions of countries for all forms of the unit value approach are quite stable, so there is much less uncertainty concerning the cross-country differences.
Keywords: F10; F14; 330; intra-industry trade; horizontal trade flows; vertical trade flows; product quality; unit values; per capita income